Loss of TDP-43 causes ectopic endothelial sprouting and migration defects through increased fibronectin, vcam 1 and integrin α4/β1 - Hipke, Katrin; Pitter, Bettina; Hruscha, Alexander; van Bebber, Frauke; Modic, Miha; Bansal, Vikas; Lewandowski, Sebastian A.; Orozco, Denise; Edbauer, Dieter; Bonn, Stefan; Haass, Christian; Pohl, Ulrich; et al. (Frontiers in Cell and Developmental Biology, 2023)
Aggregation of the Tar DNA-binding protein of 43 kDa (TDP-43) is a pathological hallmark of amyotrophic lateral sclerosis and frontotemporal dementia and likely contributes to disease by loss of nuclear function. Analysis of TDP-43 function in knockout zebrafish identified an endothelial directional migration and hypersprouting phenotype during development prior lethality. In human umbilical vein cells (HUVEC) the loss of TDP-43 leads to hyperbranching. We identified elevated expression of FIBRONECTIN 1 (FN1), the VASCULAR CELL ADHESION MOLECULE 1 (VCAM1), as well as their receptor INTEGRIN α4β1 (ITGA4B1) in HUVEC cells. Importantly, reducing the levels of ITGA4, FN1, and VCAM1 homologues in the TDP-43 loss-of-function zebrafish rescues the angiogenic defects indicating the conservation of human and zebrafish TDP-43 function during angiogenesis. Our study identifies a novel pathway regulated by TDP-43 important for angiogenesis during development.